2023
DOI: 10.3390/bs13030221
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally Responsible Purchase Intention in Pacific Alliance Countries: Geographic and Gender Evidence in the Context of the COVID-19 Pandemic

Abstract: The objectives of this research were: (1) to examine the influence of environmental awareness (EA), sustainable consumption (SC) and social responsibility (SR) on the environmentally responsible purchase intention (ERPI) of consumers in the member countries of the Pacific Alliance, namely, Chile, Colombia, Mexico and Peru; and (2) to analyze whether there is a moderating effect related to the country of residence and gender of the consumer. The study was conducted under a quantitative and cross-sectional appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 128 publications
1
2
0
Order By: Relevance
“…As expected, the country, when utilized as a moderator, revealed statistically significant differences among the three populations with regards to the percentage of variance explained in intentions. This finding is in line with the moderating effect of country that García-Salirrosas et al [ 109 ] found among the Pacific Alliance countries.…”
Section: Discussionsupporting
confidence: 89%
“…As expected, the country, when utilized as a moderator, revealed statistically significant differences among the three populations with regards to the percentage of variance explained in intentions. This finding is in line with the moderating effect of country that García-Salirrosas et al [ 109 ] found among the Pacific Alliance countries.…”
Section: Discussionsupporting
confidence: 89%
“…For instance, Roseman et al ( 101 ) highlight the importance of the connection between consumers’ attitudes toward food and their intention to buy it. Creating a positive perception among consumers is crucial, as it can significantly affect their buying and consumption behavior ( 102–104 ). Küster-Boluda and Vidal-Capilla ( 98 ) stated that consumers’ favorable attitudes toward functional foods significantly impact their likelihood of consuming them.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Environmental awareness encompasses understanding ecological issues and the fundamental relationships contributing to environmental impact (Milfont and Duckitt, 2004;García-Salirrosas et al, 2023;Guo and Xiao, 2023). This perspective emphasizes the importance of individual perception and knowledge concerning environmental problems, influencing subsequent behavioral choices García-Salirrosas et al, 2023). As a result, environmental awareness predicts pro-environmental behavior (Kaiser et al, 1999;Omarova and Jo, 2022).…”
Section: Environmental Awarenessmentioning
confidence: 99%
“…Previous studies have reported that awareness of the environment influences pro-environmental behavior Valenzuela-Fernández et al, 2023). The first dimension of the theory of planned behavior is the attitude; there is evidence that indicates a positive relationship between environmental awareness and attitudes toward environmental behavior and the likelihood of individuals engaging in green purchasing (Arundati et al, 2020;García-Salirrosas et al, 2023;Gómez-Bayona et al, 2023;Hlaváček et al, 2023). For instance, Arundati et al (2020) point out that individuals with a more environmentally solid awareness are more likely to acquire goods with a reduced environmental impact.…”
Section: Influence Of Environmental Awareness On the Theory Of Planne...mentioning
confidence: 99%